Between Dawkins And Plantinga: Notes - Mauro Sérgio Santos da Silva; Dennys Garcia Xavier (Aufklärung, 2015)
This paper contextualizes epistemologically and establishes some differences between the materialistic naturalism of Richard Dawkins and the analytical theism of Alvin Plantinga. It presents some of the main currents in contemporary philosophy of religion, especially for Anglo-American scenary, considering this scenary relevant, present and central. Then talks about the Dawkin's idea that organized complexity has no design, their criticism to the notions of chance and intelligent design, its position in favor of the theory of evolution and the theistic counter point that Plantinga develops against Dawkins.